Mechanisms of growth: social-emotional learning and the PwrHrs program - Boomsma, A'Lece J., author; Riggs, Nathaniel, advisor; Fruhauf, Christine, committee member; Portz, Jennifer, committee member (Colorado State University. Libraries, 2019)
Recent public education reform initiatives have emphasized student academic achievement, primarily in reading and mathematics. To meet the pressure these initiatives present, a growing number of schools have chosen to implement social-emotional learning (SEL) curricula and instruction to promote academic development. PwrHrs (pronounced "power hours") is an after-school initiative of YouthPower365, an organization, based in Avon, Colorado. PwrHrs seeks to enrich students' academic and social-emotional competence through supplemental academic tutoring and intentional SEL instruction. Past evaluations of the PwrHrs program have demonstrated through single-group pretest-posttest designs that PwrHrs youth have exhibited increases in reading, mathematics, and social-emotional competency. The purpose of this study was to explore the effect of PwrHrs' social-emotional learning components on gains in PwrHrs participants' academic achievement. The study used a non-randomized control group comparison design including 567 participants enrolled in three area schools during the 2017-2018 school year. Pre-, mid-, and posttest data in reading and math, as well as math and reading report card grades, were examined for differences based on PwrHrs participation and amount of exposure to PwrHrs SEL instruction. Main program effects were examined using multiple regression, controlling for appropriate covariates. Results revealed a significant effect of PwrHrs SEL instruction on reading mid-test achievement; however, this was the only significant effect found. Although few significant results were revealed, this study informs future directions for PwrHrs program design and implementation.